Evaluation of a wearable wireless device with artificial intelligence, iThermonitor WT705, for continuous temperature monitoring for patients in surgical wards: a prospective comparative study - Liu, Yuwei; Liu, Changqing; Gao, Min; Wang, Yan; Bai, Yangjing; Xu, Ruihua; Gong, Renrong (BMJ open, 2020)
ObjectivesTo evaluate a new-generation, non-invasive, wireless axillary thermometer with artificial intelligence, iThermonitor (WT705, Raiing Medical, Beijing, China), and to ascertain its feasibility for perioperative continuous body temperature monitoring in surgical patients.SettingDepartments of Biliary Surgery and Operating Room and the post-anaesthesia care unit of a university teaching hospital in Chengdu, China.ParticipantsA total of 526 adult surgical patients were consecutively enrolled.DesignThis was a prospective observational study. Axillary temperatures were continuously recorded with iThermonitor throughout the whole perioperative period. The temperatures of the contralateral armpit were measured with mercury thermometers at 8:00, 12:00, 16:00 and 20:00 every day and were used as references.Outcome measuresThe outcomes were the accuracy and precision of the temperatures measured with iThermonitor, the validity to detect fever and the feasibility of continuous wear. Pairs of temperatures were evaluated with Student’s t-test, Pearson’s correlation and repeated-measures Bland-Altman plot.ResultsA total of 3621 pairs of body temperatures were obtained. The temperatures measured with iThermonitor agreed with those measured with the mercury thermometers overall, with a mean difference of 0.03°C±0.35°C and a moderate correlation (r=0.755, p<0.001). The 95% limits of agreement (LoA) ranged from −0.63°C to 0.73°C, with 5.11% of the differences outside the 95% LoA. The intraclass correlation coefficient was 0.753. Continuous temperature monitoring captured more fevers than intermittent observation (117/526 vs 91/526, p<0.001), detected fever up to 4.35 hours earlier, and captured a higher peak temperature (0.29°C±0.27°C, 95% CI: 0.26–0.31). All subjects felt that wearing iThermonitor was more or less comfortable and did not affect their daily activities.ConclusionsiThermonitor is promising for continuous remote temperature monitoring in surgical patients. However, further developments are still needed to improve the precision of this device, especially for temperature detection in underweight patients and those with lower body temperature.Trial registration numberChiCTR1900024549; Results (registered on 5 July 2019).